POLA PENGELOLAAN PROGRAM PENDIDIKAN KESETARAAN BERBASIS KECAKAPAN HIDUP DI PKBM BENDAN JAYA KOTA PEKALONGAN - Sodik, Sodik (Educational Management, 2012)
Abstract: This study aims to determine the pattern of the management program of Life Skills-based Education Equality in PKBM Bendan Jaya Pekalongan. This study employs a qualitative case study approach. The subjects of this study were 5 managers, 27 tutors, 5 technical resource persons and 131 Citizens. The data was collected by the method of participant observation and in-depth interviews and documentation. Analysis of data is employed derived from Miles and Huberman, namely data reduction, display data and verification data. The results revealed that (1) Program Planning education in PKBM Bendan mature Jaya done that based on the potential and opportunities; (2) Implementation of Life skills-based education equality in PKBM Bendan Jaya is very flexible related to the agreement between all the elements that exist in PKBM; (3) Organization of Human Resources at PKBM Bendan Jaya is characterized by patterns of kinship and stewardship patterns which tend to follow the pattern of the dual position gendhong indhit; (4) Eventhough the equality of Education Program Evaluation of PKBM Bendan Jaya tends to be less tolerant, but the residents are found to learn the material well enough with the evidence of high graduation. Abstrak: Penelitian ini bertujuan untuk mengetahui pola pengelolaan program Pendidikan Kesetaraan berbasis Kecakapan Hidup di PKBM Bendan Jaya Kota Pekalongan. Penelitian ini menggunakan pendekatan kualitatif studi kasus. Subjek  penelitian ini adalah 5 pengurus, 27 orang Tutor, 5 nara sumber teknis dan 131 Warga Belajar PKBM Bendan Jaya. Pengumpulan data dilakukan dengan metode pengamatan terlibat dan wawancara mendalam serta metode dokumentasi. Analisis data dengan teknik analisis yang dikembangkan oleh Miles dan Huberman yaitu reduksi data, display data dan verifikasi data.  Hasil penelitian menunjukkan: (1) Perencanaan Program pendidikan di PKBM Bendan Jaya dilakukan secara matang yakni berdasarkan pada potensi dan peluang yang ada; (2) Pelaksanaan Program pendidikan Kesetaraan berbasis kecakapan Hidup di PKBM Bendan Jaya sangat fleksibel dalam arti berdasarkan kesepakatan antar semua elemen yang ada di PKBM; (3) Pengorganisasian  Sumber Daya Manusia di PKBM Bendan Jaya sangat diwarnai dengan pola kekeluargaan  dan pola kepengurusan cenderung mengikuti pola gendhong indhit; dan (4) Evaluasi Program pendidikan Kesetaraan di PKBM Bendan Jaya meski cenderung toleran  namun daya serap warga belajar terhadap materi cukup tinggi.